2018
DOI: 10.1093/annonc/mdy244
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human study of LY3039478, an oral Notch signaling inhibitor in advanced or metastatic cancer

Abstract: NCT01695005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 20 publications
1
46
0
Order By: Relevance
“…This report describes the first clinical study of crenigacestat in Japanese patients with solid tumors. Results of this phase 1, single-center, nonrandomized, single-arm, open-label, doseescalation study indicate that crenigacestat is tolerated at both the 25 mg and 50 mg doses in Japanese patients, with 50 mg TIW confirmed as the recommended phase 2 dose in this population [9].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This report describes the first clinical study of crenigacestat in Japanese patients with solid tumors. Results of this phase 1, single-center, nonrandomized, single-arm, open-label, doseescalation study indicate that crenigacestat is tolerated at both the 25 mg and 50 mg doses in Japanese patients, with 50 mg TIW confirmed as the recommended phase 2 dose in this population [9].…”
Section: Discussionmentioning
confidence: 88%
“…Crenigacestat is a potent small molecule inhibitor of Notch cleavage that prevents the release of the Notch intracellular domain by inhibiting proteolytic activity of γ-secretase complex, and thereby decreasing Notch signaling and its downstream biologic effects. A phase 1, nonrandomized, open-label, multicenter trial that evaluated the safety and antitumor activity of crenigacestat in non-Japanese patients with advanced or metastatic cancers recommended a phase 2 dose of crenigacestat monotherapy at 50 mg administered 3 times per week (TIW) during a 28-day cycle [9]. In the confirmatory, expansion trial of crenigacestat in patients with adenoid cystic carcinoma, it was demonstrated that crenigacestat has a manageable safety profile and a clinical pharmacodynamic effect on Notch-targeted genes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies targeting Notch have been initiated since a few years ago and have been mainly based in the use of GSIs, although, more recently, monoclonal antibodies against Notch receptors and ligands have been developed (Table 2). LY3039478 is a potent GSI that has demonstrated antitumor activity in xenograft models, including lung cancer [157], and in patients with distinct neoplasias [158,159], and clinical trials are currently undergoing or have just been completed in patients with advanced solid tumors and with gene/protein alterations related to the Notch pathway (NCT02836600, NCT02784795). Another GSI, RO4929097, has significant activity in blocking Notch processing and activity, and is efficacious in markedly inducing tumor growth inhibition in NSCLC xenografts [160].…”
Section: Therapy Perspectivesmentioning
confidence: 99%